Esthétique et politique dans le cinéma argentin Albertina Carri et Lucía Puenzo : des histoires de familles - Mullaly, Laurence (PrimaLun@, 2022)
Albertina Carri and Lucía Puenzo belong to the same generation, that of the post-dictatorship era, which is also that of the New Argentine Cinema. However, their fictional films represent power relationships and the forms of violence that accompany them in radically different ways. Their h/Family Stories in the Plural are examined with an undisciplined methodology that draws on cultural, feminist and gender studies. The aesthetic and political stakes, and in particular the staging of gender, class, race and sexuality relations, are put into perspective through a contextualized study in order to shed light on the links between socio-cultural production, history and politics, but also on the negotiations operated by each filmmaker in order to position herself in a globalized cinematographic field.